A New Method for Modeling Bottom Shear Stress under Irregular Waves - Taufiqur Rachman; Suntoyo Suntoyo (IPTEK The Journal for Technology and Science, 2011)
The bottom shear stress estimation is the most important step to device an input to all the practical sediment transport models. In this paper, the modeling of bottom shear stress in a rough turbulent bottom boundary layer under irregular waves of experimental result is examined by a new calculation method of bottom shear stress based on incorporating velocity and acceleration terms simultaneously. A new acceleration coefficient is proposed to formulate the bottom shear stress under irregular waves. The new formula is further examined with a basic harmonic wave cycle modified with the phase difference and square of the instantaneous friction velocity incorporating the acceleration effect as proposed by the previous researchers. The new method gave the smallest the RMSE value indicating that the new method has the best agreement with the bottom shear stress of experimental results. Therefore, it can effectively be utilized in a beach evolution model by combining it with the irregular wave transformation model.